Dreaming : a very short introduction - Hobson, J. Allan, 1933- (Very short introductions., 2005)
What is dreaming and what causes it? Why are dreams so strange and often hard to remember? Modern science has given us a new and increasingly clear picture of how dreaming is created by the brain. This book introduces sleep laboratory science, the cellular and molecular mechanisms of sleep, and explores how the science of dreaming impacts our understanding of psychoanalysis and mental illness. - ;What is dreaming, and what causes it? Why are dreams so strange and why are they so hard to remember? Replacing dream mystique with modern dream science, J. Allan Hobson provides a new and increasingl.